Circular RNA circ_0020710 drives tumor progression and immune evasion by regulating the miR-370-3p/CXCL12 axis in melanoma - Wei, Chuan-Yuan (Mol Cancer, 2020)
BACKGROUND: Circular RNAs (circRNAs) have been reported to have critical regulatory roles in tumor biology. However, their contribution to melanoma remains largely unknown. METHODS: CircRNAs derived from oncogene CD151 were detected and verified by analyzing a large number of melanoma samples through quantitative real-time polymerase chain reaction (qRT-PCR). Melanoma cells were stably transfected with lentiviruses using circ_0020710 interference or overexpression plasmid, and then CCK-8, colony formation, wound healing, transwell invasion assays, and mouse xenograft models were employed to assess the potential role of circ_0020710. RNA immunoprecipitation, luciferase reporter assay and fluorescence in situ hybridization were used to evaluate the underlying mechanism of circ_0020710. RESULTS: Our findings indicated that circ_0020710 was generally overexpressed in melanoma tissues, and high level of circ_0020710 was positively correlated with malignant phenotype and poor prognosis of melanoma patients. Elevated circ_0020710 promoted melanoma cell proliferation, migration and invasion in vitro as well as tumor growth in vivo. Mechanistically, we found that high level of circ_0020710 could upregulate the CXCL12 expression via sponging miR-370-3p. CXCL12 downregulation could reverse the malignant behavior of melanoma cells conferred by circ_0020710 over expression. Moreover, we also found that elevated circ_0020710 was correlated with cytotoxic lymphocyte exhaustion, and a combination of AMD3100 (the CXCL12/CXCR4 axis inhibitor) and anti-PD-1 significantly attenuated tumor growth. CONCLUSIONS: Elevated circ_0020710 drives tumor progression via the miR-370-3p/CXCL12 axis, and circ_0020710 is a potential target for melanoma treatment.